Konflik Pengelolaan Kawasan Cagar Alam Pulau Sempu ‘Antara Kebutuhan Konservasi dan Pariwisata' - BASYORI, BASYORI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Conflict on management of Sempu Island Nature Reserve, occurs between East Java BBKSDA with the surrounding community and with other government agencies in the area. The roots of the conflict stems from policies or regulations relating to the conservation area, which should only be used for activities that are scientific, aquaculture development, or research. But people, especially those residing in the surrounding area, has violated the rule limit to use it as a natural tourist attraction. This study was conducted using qualitative descriptive methods, trying to interpret the symptoms that occur with as comprehensive as possible. The data required in the study were primary data collected through observation and in–depth interview, and secondary data obtained by a documentation technique. The theories that is used to analyze the phenomenon of the conflict is a public dispute, the concept of governance, and boundary models as a tool for conflict analysis. The conclusion is that there are several main reasons why conflict on management of Sempu Island Nature Reserve is continuing until now, and did not immediately find a solution, namely: first, differences in perceptions among stakeholders about the existing rules; second, the Sempu Island nature reserve agencies was unable to enforce the rules as they should; third, legitimacy or jurisdiction of East Java BBKSDA much opposed by the public; fourth, the omission of the violation of rules (boundaries) that is led to the neglect of the rule. Alternative dispute resolution can be achieved is a change of rules, which could allow for the limited nature tourism activities in the region. A conflict resolution mechanisms try to present, and the opportunity for an agreement for the implementation of the new rules, which means that the new boundary (rules) will be applied.